PENARIKAN MEREK PRODUK: EFEK INDUSTRI, STRATEGI PENARIKAN DAN BAHAYA PADA KEKAYAAN PEMEGANG SAHAM - Dwi Dewianawati (STIE Mahardhika, 2020)
The purpose of this paper is to provide insight into the impact of product recalls on manufacturing company shareholders in various supply chains. Previous research investigating this phenomenon was dominated by sectoral units and/or did not recognize threat interactions, policy recalls and sectors. Using the case study process, the study explored investor responses to key market product recall characteristics, recall policies and hazard levels, in a cross-industry survey of 295 product recall notices. The findings revealed a strong negative response from the share price to product recalls and a significant variation between the type of business and its level of danger. More controlled and tighter supply chains, such as the car and pharmaceutical markets, have shown statistically substantial share price declines. The findings suggest that the business sector and the level of harm associated with defective goods are major factors affecting the shareholders of manufacturing companies. Contrary to some reports, the effects of the recall policy have not been verified, although the recall campaign has proactively, in some cases, contributed to the rise in the share price. This study will further benefit from a more thorough investigation of recall strategies on business assessments in certain industries, especially those vulnerable to regular and expensive product recalls.